Development of cooking skills questionnaire for EFNEP participants in Kansas - Frans, Nike (Kansas State University, 2017)
There have been major shifts in the dietary patterns of people in the United States in the last four decades. People eat fast food more frequently, eating more convenience food products, and highly processed food. On the other hand, the practice of cooking from raw ingredients or cooking from scratch has been declining. The lack of cooking skills is one of the barriers of cooking from raw ingredients. Cooking skills are one of the important determinants of food choice. People who have higher cooking skills tend to choose healthier food options. There are many programs that aim to increase cooking skills and nutrition knowledge. One of them is done by EFNEP. Over the years, EFNEP has been helping the low socioeconomic population to reach nutritional well-being. Evaluation is an important component of EFNEP. There are evaluation tools in EFNEP including behavioral checklist and dietary recall that are administered pre and post program. However, these tools do not specifically measure participants’ cooking skills. A proposed short self-reported questionnaire is designed to measure cooking skills of EFNEP participants in Kansas. The questionnaire comprises of seven questions and has been tested to a representative group.
Keywords: Cooking skills questionnaire; Expanded Food and Nutrition Education Program; Cooking skills measurement; Cooking skills